The role of stop‐signal probability and expectation in proactive inhibition. (1st April 2015) - Vink, Matthijs; Kaldewaij, Reinoud; Zandbelt, Bram B.; Pas, Pascal; du Plessis, Stefan
Abstract: The subjective belief of what will happen plays an important role across many cognitive domains, including response inhibition. However, tasks that study inhibition do not distinguish between the processing of objective contextual cues indicating stop‐signal probability and the subjective expectation that a stop‐signal will or will not occur. Here we investigated the effects of stop‐signal probability and the expectation of a stop‐signal on proactive inhibition. Twenty participants performed a modified stop‐signal anticipation task while being scanned with functional magnetic resonance imaging. At the beginning of each trial, the stop‐signal probability was indicated by a cue (0% or > 0%), and participants had to indicate whether they expected a stop‐signal to occur (yes/no/don't know). Participants slowed down responding on trials with a > 0% stop‐signal probability, but this proactive response slowing was even greater when they expected a stop‐signal to occur. Analyses were performed in brain regions previously associated with proactive inhibition. Activation in the striatum, supplementary motor area and left dorsal premotor cortex during the cue period was increased when participants expected a stop‐signal to occur. In contrast, activation in the right inferior frontal gyrus and right inferior parietal cortex activity during the stimulus‐response period was related to the processing of contextual cues signalling objective stop‐signal probability, regardless of expectation. These data show that proactive inhibition depends on both the processing of objective contextual task information and the subjective expectation of stop‐signals. Abstract : The subjective belief of what will happen plays an important role across many cognitive domains, including response inhibition. Here we investigate the effects of stop‐signal probability and the expectation of a stop‐signal on proactive inhibition. We show for the first time that the striatum is engaged during the initial phase of a trial if participants expect a stop‐signal to occur, while activation in the right inferior frontal gyrus is modulated by stop‐signal probability later during the trial. These data show that proactive inhibition depends on both the processing of objective contextual task information and the subjective expectation of stop‐signals.